TNNT1-associated nemaline myopathy: a rare case report from a tertiary centre in central India - Bhavanagare, Mukesh; Vishnu, Shilpa Pallithrikkovil; Kamble, Shubham; Chandel, Anuragsingh; Chauhan, Varsha (International Journal of Contemporary Pediatrics, 2025)
Nemaline myopathy (NM) is a rare congenital skeletal muscle disorder characterized by generalized muscle weakness and the presence of rod-like nemaline bodies within muscle fibers. Severity varies from neonatal hypotonia and respiratory failure to milder forms with delayed motor milestones. Inheritance is autosomal dominant or recessive, with mutations commonly in ACTA1, NEB, TPM3 and TNNT1. We report a case of a 3-year-old female with global motor delay, feeding difficulties and hypotonia. Whole exome sequencing revealed a homozygous TNNT1 variant (c.33-2A>T), confirming NM. Supportive care, including nutritional and physiotherapy intervention, led to clinical improvement. This report emphasizes the importance of early clinical suspicion and genetic evaluation in NM, particularly in consanguineous populations.